Are the adverse psychiatric outcomes reflection of occupational stress among nurses: An exploratory study - Davey, Anuradha; Sharma, Parul; Davey, Sanjeev; Shukla, Arvind; Srivastava, Kajal; Vyas, Shaili (Asian Journal of Medical Sciences, 2015)
Background: Stress-related disorders encompass a broad array of conditions, including psychological disorders such as depression and anxiety etc. Among healthcare professionals, nurses have been found to be most prone to burnout. Aims and Objective: 1) To find out the prevalence of recent stress among staff nurses in terms of somatic symptoms, anxiety, social dysfunction and depression and; 2) To find out the association between these psychiatric outcomes and various socio-demographic variables, inter-personal relationships, working environment and professional stress. Materials and Methods: Institutional based cross sectional study conducted on 100 staff nurses. Goldberg and Hillier’s 28-item scaled version of the General Health Questionnaire (GHQ-28) was used to measure the psychological aspect of quality of life of Staff nurses. Results: The most common psychological outcome noted was the social dysfunction (94%) among the staff nurses. For anxiety, potential stressor were doctors’ attitude, insufficient salary and separate wash room for females; whereas significant association was found between depression and unsatisfactory attitude of doctors, fellow nurses, not enough time for rest and not getting enough holidays. Conclusion: Social dysfunction could be cause or effect of other psychiatric manifestations like anxiety or depression Asian Journal of Medical Sciences Vol.7(1) 2015 96-100